Single Blastocyst-Stage Embryo Transfer should be Promoted for IVF Cycles Using Donor Sperm (IVFD) - Mingzhao Li; Xia Xue; Juanzi Shi (Clinical and Experimental Obstetrics & Gynecology)
Background: Twin pregnancies carry significant fetal, perinatal and maternal risks. Thus, it is important to evaluate clinical outcomes of in vitro fertilization with donor sperm (IVFD) in the first attempt with double cleavage-stage embryos and explore optimal number of day 3 high-quality embryos for the blastocyst transfer on day 5. Methods: We retrospectively identified all IVFD embryo transfers (IVFD-ETs) for the initial time between 2014 and 2021 at our hospital. We mainly analyzed the twin pregnancy rates for double day 3 embryo transfers and clinical outcomes of day 5 blastocyst transfers by prolonged culture with different numbers of day 3 high-quality embryos. Results: Among 1512 IVFD-ETs, 834 were day 3 embryo transfers and 678 were day 5 blastocyst transfers. Our data indicated that the twin pregnancy rates reached up to 40% in the 674 double cleavage-stage embryo transfers and it was not due to the quality of the transferred embryos. For prolonged culture with 2, 3 and 4 day 3 high-quality embryos, the cycle rates of no high-quality blastocysts obtained were 30.43%, 19.80% and 7.91%, respectively. The clinical pregnancy rates were 56.52%, 74.26% and 72.32%, respectively. The twin pregnancies rates were 7.69%, 14.67% and 6.77%, respectively. Conclusions: Transferring double cleavage-stage embryos had high risks of twin pregnancies in the IVFD-ETs. Blastocyst transfer was safe and recommended for the patients with three or more high-quality embryos on day 3.